2022
DOI: 10.1039/d1ta10678c
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale production of a low-cost molybdenum dioxide–phosphide seamless electrode for high-current-density hydrogen evolution

Abstract: Herein, we report the large-scale production of a molybdenum oxide-phosphide (MoO2-MoP) seamless electrode (SE) that is vertically grown on cheap industrial-grade molybdenum substrates (e.g. molybdenum plate, molybdenum mesh, or molybdenum...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Notably, Co 0.59 Ni 0.41 C 2 O 4 @PANI/NF also has advanced catalytic activity at high‐current‐density of −1000 mA cm −2 (Figure 3g; Tables S5, and S6, Supporting Information). [ 43,45–60 ]…”
Section: Resultsmentioning
confidence: 99%
“…Notably, Co 0.59 Ni 0.41 C 2 O 4 @PANI/NF also has advanced catalytic activity at high‐current‐density of −1000 mA cm −2 (Figure 3g; Tables S5, and S6, Supporting Information). [ 43,45–60 ]…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, they also successfully constructed a molybdenum oxide-phosphide (MoO 2 -MoP) seamless electrode on Mo substrate using the same method. 274 The MoO 2 -MoP mesh electrode achieved an industrial current density of 800 mA cm À2 at a low overpotential of 362 mV and showed excellent stability at high current densities for 200 h in an alkaline electrolyte. Additionally, it yielded a current density of 1000 mA cm À2 at 293 mV in 1.0 M KOH solution, but required an overpotential of only 215 mV to reach the same current density in 5.0 M KOH solution, which was practical for industrial alkaline HER.…”
Section: Molybdenum-based Substratesmentioning
confidence: 95%
“…Reproduced with permission. [ 73a ] Copyright 2022, Royal Society of Chemistry. Reproduced under the terms of CC‐BY license.…”
Section: The Primary Demands For Designing Electrocatalysts For Indus...mentioning
confidence: 99%